STUDY OF PHYSICAL CHARACTERISTIC OF NETSS FROM PE (POLYETHYLENE) WITH DIFFERENT DIAMETER SOAKED OF FRESH WATER AND SEA WATER - Indah Bustari; Isnaniah Isnaniah; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            This research was conducted on 27 November 2017 to 21 January 2018 which was held in laboratory of Fishery and Marine Fishery Resources Utilization Faculty, University of Riau. The purpose of this research to know the change of physical characteristics of nets yarn of PE (Polyethylene) material with different diameter soaked in sea water and fresh water. The method used in this research the experimental method, the data change of thenets yarn length obtained are processed according to the formula SNI 08-00889-1989 and then analyzed descriptive. From the observation according to SNI 08-0889-1989 that the PEØ 0.5 mm, 0.8 mm and 1.0 mm experience changes the characteristic of the nets yarn after soaked for 50 days in fresh water and sea water.  The change in the length of mesh yarns soaked in sea water influential when compared to soak in fresh water and each diameter experience changes length different. The largein diameter of the PE then the longer the length of the nets yarn change. Key word :Study changes the physical characteristics of nets yarnsPE, Materials of fishing netsPE, changes in length and elongation of the yarnPE.